The antimicrobial activity of ETD151 defensin is dictated by the presence of glycosphingolipids in the targeted organisms - Ons Kharrat; Yoshiki Yamaryo-Botté; Rouba Nasreddine; Sébastien Voisin; Thomas Aumer; Bruno P. A. Cammue; Jean-Baptiste Madinier; Thomas Knobloch; Karin Thevissen; Reine Nehmé; Vincent Aucagne; Cyrille Botté; et al. (Proceedings of the National Academy of Sciences, 2025)
Fungal infections represent a significant global health concern, with a growing prevalence of antifungal drug resistance. Targeting glucosylceramides (GlcCer), which are functionally important glycosphingolipids (GSL) present in fungal membranes, represents a promising strategy for the development of antifungal drugs. GlcCer are associated with the antifungal activity of certain plant and insect defensins. The 44-residue ETD151 peptide, optimized from butterfly defensins, is active against several fungal pathogens. ETD151 has been shown to induce a multifaceted mechanism of action (MOA) in Botrytis cinerea , a multiresistant phytopathogenic fungus. However, the target has yet to be identified. Our findings demonstrate that the presence of GlcCer in membranes determines the susceptibility of Pichia pastoris and Candida albicans toward ETD151. To ascertain whether this is due to direct molecular recognition, we demonstrate that ETD151 selectively recognizes liposomes containing GlcCer from B. cinerea , which reveals a methylated-sphingoid base structure. The dissociation constant was estimated by microscale thermophoresis to be in the µM range. Finally, fluorescence microscopy revealed that ETD151 localizes preferentially at the surface of B. cinerea . Furthermore, the majority of prokaryotic cells do not contain GSL, which explains their resistance to ETD151. We investigated the susceptibility of Novosphingobium capsulatum , one of the rare GSL-containing bacteria, to ETD151. ETD151 demonstrated transient morphological changes and inhibitory growth activity (IC 50 ~75 µM) with an affinity for the cell surface, emphasizing the critical importance of GSL as target. Understanding the MOA of ETD151 could pave the way for new perspectives in human health and crop protection.